Mathematical Creativity in Elementary School Children: General Patterns and Effects of an Incubation Break - Shaw, Stacy T.; Luna, Michelle L.; Rodriguez, Briana; Yeh, Jan; Villalta, Nancy; Ramirez, Gerardo (Frontiers in Education, 2022)
Research from the general field of creativity demonstrates that in the realm of problem-solving, breaks from the task at hand, known as incubation breaks, can improve idea generation and creative thinking. This study investigated whether a brief incubation break during a mathematical strategy generation task could improve elementary students’ ability to generate strategies and think more creatively. Over 200 elementary school students (grades 1 - 5) were asked to continuously generate mathematical strategies to solve the problem 36 - 18 for 10 minutes, with half randomly assigned to receive a one-minute incubation break after 5 minutes. Results showed that children assigned to the incubation break showed a statistically significantly higher number of strategies generated in the second block of the working period compared to students who received no break, but there were no differences in rated creativity of their strategies. Further exploratory analyses found that across grades, the number of strategies students could produce on average increased with each grade. However, when it came to the creativity of strategies, a linear trend emerged only from first through fourth grade, but fifth-grade students showed a drop in creativity.